THE STUDY ON FOOTBALL CLUB PERFORMANCE MANAGEMENT A CASE OF THE ENGLAND FOOTBALL ASSOCIATION - Zijing, Wang; Yinru, Chen (ASEAN Journal of Sport for Development and Peace, 2022)
Sports performance management is increasingly essential for national sports organizations because it aims to control the business with stakeholder goals and satisfaction. This is especially true in the increasingly competitive football business. Some previous studies have suggested that football clubs need an essential element of effective management to excel in this competitive environment. Management of football clubs is necessary to meet the expectations of various stakeholder groups. Other previous studies generally agree that management processes enable effective management of individuals and teams to improve the level of performance in an organization. The Institute of Personnel Management (1992) also noted that performance management is a strategy that engages organizations through staffing policies, cultures, styles, and communication systems developed for different activities. An important role that performance management plays in improving strategic synergy. This study provides an overview of sports performance management methods commonly used by English football clubs and a detailed analysis of the numerous performance measurement methods and obstacles that affect the effectiveness of governmental sports organizations. A systematic evaluation of the studies was used as one of the analyses methods. Recent research is evaluated critically. Take, for instance, the English Football Association. It looks at various aspects of performance measurement methods being used proficiently in performance management in the public sports industry and an overview of the challenges affecting sports organizations' performance. The study presents the definition of sports performance management the background of Organization A. It Outlines common methods of sports performance management, different performance measurement techniques, and the challenges that affect the performance of sports organizations. The results show that the sports performance management and measurement of non-profit sports organizations is necessary to support non-profit sports organizations about their future development. The limitations in the study were also included. (1) Sports performance management methods and performance measurement techniques need to be studied. (2) Available information publicly for football clubs to provide enough detailed organizational performance challenges. (3) More questionnaires or interviews are needed in future studies.